POPULATION GENETIC STRUCTURE OF THREE RIVERINE POPULATIONS OF CATFISH, WALLAGO ATTU (BLOCH & SCHNEIDER, 1801) USING MICROSATELLITE DNA MARKERS - Sing, Akhilesh; Lakra, Wazir S; Mandhan, Rishi Pal; Goswami, Mukunda (Journal of Indian Fisheries Association, 2014)
Five microsatellite loci were analyzed to interpret population genetic structure of the Indian fresh water catfish, Wallago attu collected from three riverine locations Gomti, Ken and Brahmaputra in India. The five loci were polymorphic  in all three populations. The populations varied in the number and frequencies of alleles as well as heterozygosities in the loci analyzed. Population pairwise differentiation (FST)  value was significant between Ken and the Brahmaputra population. Relatively high level of gene flow and low level of FST values were found between the Gomti and the Brahmaputra population. The unweighted pair group method with averages (UPGMA) dendrogram based on Nei’s genetic distance revealed two clusters: the Brahmaputra population was alone in one cluster whereas the Gomti and the Ken made another cluster. The results indicate a relatively low level of genetic variability among the three riverine populations. The present study will be useful for conservation and management of natural population and stock enhancement of Wallago attu across India. Key words: Wallago attu, microsatellite, population structure, conservation genetics.